Decaffeination of robusta (Coffea canephora) green beans using enzymes from various types of fruit juice - Silitonga, Anggriani Elfrida; Sinaga, Hotnida; Silalahi, Jansen (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Robusta and Arabica are the two most widely cultivated coffee varieties in Indonesia, with Robusta typically exhibiting a higher caffeine content than Arabica. Caffeine is the primary compound in coffee, contributing to improved psychomotor performance and various physiological effects, including increased energy levels. According to SNI 01-7152-2006, the maximum recommended daily intake of caffeine in food or beverages is 150 mg/day or 50 mg/serving. This study aimed to reduce the caffeine content of coffee through an enzymatic approach using protease enzymes, based on the premise that protein degradation in the coffee bean membrane would lower caffeine content. Protease enzymes were derived from pineapple juice, papaya juice, chayote juice and ginger juice and determines the best soaking time. In the initial phase, the juice concentration most effective in reducing caffeine content was identified.. Factor 1 was the type of juice with 4 treatment levels (pineapple juice, papaya juice, chayote juice, and ginger juice) and factor 2 was the percentage of juice with 5 treatment levels (10%, 20%, 30%, 40% and 50%). Before the fermentation process, the caffeine content in Robusta coffee beans was 2.134%. However, after the enzymatic process involving various juice extracts, caffeine content decreased significantly, ranging from 1.295% (chayote extract) to 1.411% (pineapple extract). The optimal concentrations for reducing caffeine content were 40% pineapple juice, 50% papaya juice, 50% chayote juice, and 40% ginger juice. Then, decaffeination was carried out with variations in soaking time. Factor 1 was the best type of juice which includes 4 treatment levels (40% pineapple juice, 50% papaya juice, 50% chayote juice and 40% ginger juice) and factor 2 was the soaking time with 3 treatment levels (12 hours, 24 hours and 36 hours). Caffeine content decreased from 1.180% at 12 hours to 1.003% at 36 hours of soaking. The results indicated that prolonged soaking reduced caffeine, protein, and fat levels, but increasing moisture content and improving the cupping value of coffee beans.